'The do-gooders and scroungers': examining narratives of foodbank use in online local press coverage in the West Midlands, UK. (1st October 2020) - Price, Catherine; Barons, Martine; Garthwaite, Kayleigh; Jolly, Andrew
Abstract : This qualitative study using a grounded theory approach, assesses the construction of claims in online news articles and below the line comments in connection with foodbank use in the West Midlands region, UK. The sample includes 146 online news articles and 132 below the line comments, commencing 23 September 2010 until 8 April 2019. Individual foodbank users' stories are told and these relay discourses of stigma, shame, embarrassment and desperation. In contrast, the below the line comments centre on the undeserving poor. Here, emphasis is on the migrants who are 'flooding' the country, and the scroungers who are work-shy.